Determination of the environmental tax on the basis of modified input-output Leontief-Ford model - Liashenko, Olena; Khrushch, Lesya (Technology audit and production reserves, 2018)
The object of research is the planning of production activities, which aims to harmonize the environmental and economic criteria for the development of «nature-production». One of the most problematic places in production is environmental factor consideration, since production activity has a negative impact on the environment. The reduction of the greenhouse gases share in emissions from industrial enterprises is important particularly. Approaches to production activity modeling on the basis of inter-industry balance with environmental component are used in the course of the study. The modified ecology-economic Leontief-Ford model for the case of expanding of input-output balance taking into account the new branch that carries out the processing of greenhouse gases is analyzed in the paper. The proposed model has a feature that allows to consider the process of greenhouse gases eliminating as a separate branch of production, inextricably linked by inter-branch links with other industries. Calculations based on real data of input-output balance for 2016 are carried out. An aggregated matrix of direct costs is formed with the allocation of 8 major branches. This ensures the possibility of obtaining explicit formulas for finding or assessing the magnitude of the environmental tax, depending on the pollution of the technology. In the investigation Leontief-Ford model is redesigned to a static model of input-output balance by taking into account the emergence and functioning of a new industry – the destruction of greenhouse gases. As a result of new branch introduction the matrix of direct technological costs and the matrix of direct costs increments are obtained. The price of basic products and the cost of destroying pollutants are calculated. Compared to similar well-known models, it is possible to conclude that the proposed model provides benefits when calculating the charge for pollution. As a result, the formula for finding or estimating the value of environmental tax, depending on the contamination of the technology, is implemented. The introduction of a tax rate that takes into account the contamination of production will contribute to a more rational use of the environment and, accordingly, to reduce greenhouse gas emissions to the atmosphere.